Ameloblastic fibro-odontoma in the mandible - Clinical, radiological and surgical aspect - Divya Bharat; Jayesh Vahanwala; Ashok Dabir; Prachi Jobanputra (Elsevier, 2021)
Ameloblastic fibro-odontoma (AFO) is a benign, epithelial odontogenic tumour with odontogenic mesenchyme. It shows histologic features of both ameloblastic fibroma and complex odontoma. It is a rare mixed odontogenic tumour. It occurs predominantly in children and young adults, with a slight predilection for males. It is often located in the posterior aspect of the mandible. It may either be asymptomatic or present as a painless swelling.This report describes the case of a 13-year-old girl with AFO in the right posterior mandibular region, treated conservatively with enucleation and curettage.